A Review of Magnetostatic Field Derivation Techniques in Reluctance Motors and Possible Extensions to Segmented Design - Ramon Florentino Santos; Lew Andrew Tria (Machines)
An area of study for reluctance motors is the analytical computation of their magnetic field distribution, from which other quantities, such as phase inductances and output torque, may be derived. While numerical or iterative methods exist, analytical derivations of reluctance motor magnetic fields from first principles result in solutions that are less time-consuming to implement while requiring only the motor dimensions, without the need to re-discretize the motor model. A discussion of analytical derivations is scarce in the current literature, whose focus is usually on their direct application in various motor models. This work, then, aims to review and examine the major mathematical techniques and assumptions used to derive the magnetostatic field distribution in reluctance motors. The methods under review are air gap permeance, magnetic potential, and conformal mapping techniques, and they are applied to machines with conventional structures. Other relevant approaches that can extend these techniques are also presented. Segmented motor designs have also emerged given their advantages, so they must be systematically studied. These segmented topologies may require a new set of boundary conditions before these techniques can be applied. Thus, the methods’ possible avenues of application to segmented motors are discussed as well.